Education : A Very Short Introduction - Thomas, Gary (Oxford Oxford University Press, 2013)
From the schools of ancient times to the present day, Gary Thomas looks at how and why education evolved as it has. By exploring some of the big questions, he examines the ways in which schools work, considers the differences around the world and concludes by considering the future of education worldwide.
Include Illustrations, References and Index.
A Very Short Introduction.
Keywords: Education -- Education--Philosophy